A study of the reading interests of freshman students of St. Scholastica's Academy, Marikina - Abad, Lilia L. (1983)
This study arises from the librarian's need to know the reading interests of students and to meet the challenge of giving the right book to the right reader at the right time. This concern can be well met only if librarians know what reading experiences are likely to be most valuable to a particular student.